HUBUNGAN ATRIBUT KERJA PERAWAT YANG BEKERJA SAMBIL MENEMPUH PENDIDIKAN - Sinaga, Febriyanti; Simbolon, Idaui (JURNAL ILMIAH OBSGIN : Jurnal Ilmiah Ilmu Kebidanan & Kandungan P-ISSN : 1979-3340 e-ISSN : 2685-7987, 2023)
Simultaneously working as a nurse and attending college can provide long-term benefits to the nurse, such as better career opportunities and greater competency development. However, it can also result in a significant increase in stress levels. This study aims to: 1) describe the levels of stress, depression, and anxiety of nurses who work while studying, 2) whether there is a difference between the levels of stress, depression and anxiety of nurses who work while studying. This study uses Quantitative descriptive correlational with cross-sectional data collection by purposive sampling where the sample is nurses who work while studying with a total sample of 34 people. This study found that the anxiety level of nurses who work while studying at the faculty of nursing science at Adventist University of Indonesia is mild. While the level of depression and stress is on the normal scale. Thus nurses who work while studying at the faculty of nursing science at Adventist University of Indonesia have a higher level of anxiety than the level of stress and depression. It is recommended that future researchers examine the coping strategies of nurses who work while studying qualitatively so that they can be used by future nurses not to be afraid to continue their studies while working.